2019
DOI: 10.12669/pjms.35.5.369
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune cytopenias in chronic lymphocytic leukemia

Abstract: Objective: To determine the frequency of autoimmune cytopenias in chronic lymphocytic leukemia. Methods: This cross sectional study was carried out at Department of Hematology, Army Medical College Rawalpindi, in collaboration with Military Hospital Rawalpindi and Armed Forces institute of Pathology Rawalpindi from 1st January 2018 to 1st October 2018. Sample size of 64 was calculated using WHO calculator. Age and gender of patients was noted. Frequency of autoimmune hemolytic anaemia, immune thrombocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The mean age of the patients in our study was 65.8 ± 1.5 years with the maximum number of patients falling in the group of 71-80 years. While in another local study by Ehsan AY et al, 6,7 the mean age of cohort was 62.84 years. The majority of the patients in our study were male, i.e.…”
Section: Discussionmentioning
confidence: 85%
“…The mean age of the patients in our study was 65.8 ± 1.5 years with the maximum number of patients falling in the group of 71-80 years. While in another local study by Ehsan AY et al, 6,7 the mean age of cohort was 62.84 years. The majority of the patients in our study were male, i.e.…”
Section: Discussionmentioning
confidence: 85%
“…A total of 16 studies met the inclusion criteria (n = 1264 patients) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. The summary of the included studies is provided in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The mean age across 13 of the included studies was 59 ± 6 years. Eight studies described the general hematologic and clinical profile of CLL patients who sought care at their respective institutes [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The authors reported the prevalence of abnormalities noted in the patients’ complete blood profiles such as anemia, thrombocytopenia, and elevated total leukocyte count.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of CLL, autoimmune hemolytic anaemia is the most prevalent cytopenia. Haemorrhagic necrosis of the blood is characterised by a high reticulocyte count and a positive direct antiglobulin test, as well as elevated serum bilirubin levels (17) . Also, there were statistical significant differences between the three stages regarding CD38, β2 microglobulin and TEMs percentage where highest levels were associated with Binet stage C group.…”
Section: Discussionmentioning
confidence: 99%